2014
DOI: 10.4236/jss.2014.23009
|View full text |Cite
|
Sign up to set email alerts
|

Apply Ground Theory to Interpret Escapist Experiences in Mudanwan Villa

Abstract: . The pleasure value implies that the escapists can enjoy the space, experience the environment nearby, and actively use any facilities here in the villa. The wealth value suggests that those people who come to the villa are able to afford the high price. The value of social recognition means that escapist experiences in this unique destination become a status symbol to share with others. This study provides useful information for managers to design a unique experiencescape particularly perhaps to attract inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The aforementioned finding also suggests that users who use SNSs to gratify their need to escape reality perceive SNA entertaining and engaging. Escapism experience needs immersion, participation and engagement (Chen, Gau, & Wu, 2014). Zhou and Bao (2002) identified that the positive causal relationship between social escapism motive and users’ attitude towards the Internet advertising is influenced by their perception of the Internet advertising as entertaining.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned finding also suggests that users who use SNSs to gratify their need to escape reality perceive SNA entertaining and engaging. Escapism experience needs immersion, participation and engagement (Chen, Gau, & Wu, 2014). Zhou and Bao (2002) identified that the positive causal relationship between social escapism motive and users’ attitude towards the Internet advertising is influenced by their perception of the Internet advertising as entertaining.…”
Section: Discussionmentioning
confidence: 99%
“…However, the escape experience does not significantly impact tourists' satisfaction (H2d). An escape experience requires tourists to take the initiative or fully immerse themselves in a virtual or natural environment to participate in wellness tourism activities [132], pay attention to the interpersonal interactions in the activities, and comprehensively experience situations that differ from the usual environment to obtain the spiritual enjoyment of escape from reality and produce emotional resonance. However, due to the infrastructure, layout planning, and other supporting service settings of China's wellness tourism destinations, they are still in the stage of improving efficiency and quality.…”
Section: Discussionmentioning
confidence: 99%
“…Escapism can also be the process of leaving the daily struggles, visiting a particular location, fantasizing about being in a different time and place, or assuming a different role and personality (Triantafillidou and Patala, 2016). Therefore, individuals who engage in escapist experiences make a conscious effort to utilize their time in a productive manner, based on their personal preferences, by temporarily disengaging from their routine activities (Chen et al ., 2014). However, escapism requires a considerable amount of focus and involvement as it involves an inward, self-motivated disposition that can solely be achieved through active engagement (Mathwick et al ., 2001; Wu and Liang, 2009).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%